Celebrating IWD 2021: Focus on women in gender research and leadership – Alessandra Galié - Galiè, Alessandra (International Livestock Research Institute, 2021)
Alessandra Galié, leader of ILRI’s gender team, shares how the team is taking stock of the available information on gender and livestock, identifying knowledge gaps and developing a research agenda that addresses these gaps. She urges scientists in the One CGIAR to harness synergies across the various agricultural commodities and systems to address gender issues more comprehensively and effectively.